ANALISIS AFFRORDABILITAS HUNIAN DI KAWASAN PERKOTAAN: STUDI KASUS JAKARTA - Buhaerah, Pihri (Puslitbang Kebijakan dan Penerapan Teknologi (PKPT), Kementerian PUPR, 2018)
The level of affordable housing in Jakarta is at a very critical moment. For this reason, this study aims to contribute to the discourse of affordable housing in Jakarta. In particular, this paper looks at the evidence of affordable housing situation in Jakarta. To achieve the objective of this study, data was collected from secondary sources and employed percentage of household income spent on housing related expenses as an affordability indicator. This paper argues that housing is generally affordable when household spend less than 30 per cent of their income on housing related expenses. This study finds that lower-income households are facing a greater affordability problem because net wages growth is far lower than the growth of commercial housing price. With the average net income level stands at Rp 4 million, it is clearly seen that the majority of Jakarta residents will not be able to buy a house. Therefore, this study concludes that housing price in Jakarta is no longer affordable. This study also finds that greater relying on market based-housing policy does not solve affordable housing problem in Jakarta especially for lower-midlle income households.